Estudo e desenvolvimento de uma rede linear de antenas de microfita com feixe chaveado e de um receptor Homódino para aplicação em banda ISM - Barbosa, Vinicius Ludwig (2016)
Considering a scenario of switched-beam system aiming to cover a 60º sector provided by four distinguished radiation patterns and control of sidelobe levels, this work presents the design of a four-element linear antenna array and a homodyne front-end for application in ISM Band. For the antenna array, the project flow is detailed for the optimization of the single E-shaped microstrip anntenna which composes the linear array. Additionally, this document presents the optimization method applied for the radiation pattern synthesis. The Particle Swarm Optimization (PSO) is described, including algorithm flow, parameters and implementation for sets of excitation coeficients that provide the radiation patterns required. Regarding the front-end, this document presents the design procedure to define each receiver stage and receiver chain for a homodyne receiver. The prototype of the antenna array and front-end channel were built and measured data were compared to theorical and simulation results. Very good agreement between the results validates the prototypes.